Making standards useful in the classroom - Marzano, Robert J. 4 0 16; 1969- Haystead, Mark W.; 5 Association for Supervision and Curriculum Development (Alexandria, VA : Association for Supervision and Curriculum Development, 2008)
The authors explain why they believe the standards movement in the U.S. has failed to improve classroom instruction and assessment, answer questions about how to convert standards documents into a useful format teachers can actually use, and provide scoring scales with sample measurement topics for language arts, math, science, social studies, and life skills.
Includes bibliographical references (p. 291-292).
Professional;Professional
Keywords: 2 -- 0; 6; Standards -- Education;Educational evaluation;Grading and marking (Students);Education;Educational evaluation;Grading and marking (Education) -- United States.;United States.;United States.;United States.;United States; 20; 2